INVESTIGATION OF PROTEOLYTIC AND LIPOLYTIC ACTIVITIES OF LACTIC ACID BACTERIA ISOLATED FROM AUTOCHTHONOUS TRAVNIČKI/VLAŠIĆKI CHEESE - Alkić-Subašić, Mersiha; Sakić-Dizdarević, Svijetlana; Dizdarević, Tarik; Operta, Sabina; Tahmaz, Jasmina; Đulančić, Nermina (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Lactic acid bacteria (LAB) found naturally in some foods, participate in food fermentation processes and are intentionally added as starter cultures in food industry. In traditional products, LAB appears to play a role in ripening and the development of the final organoleptic qualities. The objective of this study was to investigate proteolytic and lipolytic activities of LAB, primary isolated from traditional Travnički/Vlašićki cheese. Forty-one strain of LAB were preliminary characterized using morphological, physiological and biochemical tests. Four genera of the bacteria were included in the study: 1. Lactobacillus (Lb. paracasei/casei and Lb.brevis), 2. Pediococcus (P. pentosaceus and P. acidilacti), 3. Leuconostoc (Leu. mesenteroides) and 4. Enterococcus (E. faecalis, E. faecium and E. durans). Seven LAB strains demonstrated extremely good proteolytic activity, with proteolysis zone diameters between 14 and 18 mm. In addition to the above, low lipolytic activity of LAB originating from Travnički/Vlašićki cheese was confirmed. Proteolytic strains of BMK could find application in semi-industrial production of white brine cheese, those would positively affect more intensive proteolysis and accelerate the process of cheese ripening.